MANAGERIAL ACCOUNTABILITY, PEDAGOGICAL COMPETENCE, AND SPIRITUAL COMPETENCE OF PRINCIPALS ON TEACHER PERFORMANCE OF STATE MADRASAH ALIYAH - Abdullah, Wawan; Tarihoran, Nafan; Supardi, Supardi; Saenong, Farid F.; Syarifuddin, Encep; Fauzi, Anis; Ma’mur, Ilzamuddin (JURNAL EDUSCIENCE, 2025)
Purpose- This study aims to analyze the effect of madrasah principals' managerial accountability, pedagogical competence, and spiritual competence on teacher performance at the State Madrasah Aliyah (MAN) in Banten, Indonesia. The study counteracts the paradox of continual low performance among teachers in Islamic schools despite implementing several reform efforts.Methodology- A sample of 163 MAN teachers (a purposive sampling) was used for the quantitative inferential study. Information was gathered through questionnaires, structured observations, interviews, and documentation. At the same time, there were validated and reliable instruments for every variable: management accountability (X₁), pedagogic competence (X₂), spiritual competence (X₃), and teacher performance Y). Statistical analyses included classical assumption tests, partial correlations, multiple regression, and ANOVA.Findings- Results of this study show that all the independent variables have a significant and positive influence on teachers' performance, where 78.2% combined contribution. The latent variable of pedagogical competency had the most significant partial effect on work environment (β = 0.452), followed by spirituality competence (β = 0.390) and managerial accountability (β = 0.125). These findings demonstrate the significance of pedagogical competencies in professional practice and confirm the vital importance of moral leadership and internalized spiritual foundations.Contribution- Our study is of empirical significance as it decontextualizes spiritual competence from a religious virtue for personal development and considers spirituality not only to be among the teacher's individual traits, but also a measurable expertise essential to good practice in Islamic education. This study contributes to the literature by examining the link between management accountability and teacher performance at the classroom level, which has not often been examined in previous research.